ChemInform Abstract: Reactivity of 2‐Methyl‐4H‐3, 1‐benzoxazin‐4‐ones and 2‐Methyl‐4H‐pyrido[2, 3‐d][1, 3]oxazin‐4‐one under Microwave Irradiation Conditions. Issue 18 (17th April 2014) - Prousis, Kyriakos C.; Tzani, Andromachi; Avlonitis, Nicolaos; Calogeropoulou, Theodora; Detsi, Anastasia
Abstract: Reaction of the title oxazinones (III) with C‐nucleophiles (IV) under microwave irradiation conditions gives fused pyridine derivatives (V) in good yields.